1999
DOI: 10.1002/1522-7189(199911/12)7:6<283::aid-nt70>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A review of the volatile metabolites of fungi found on wood substrates

Abstract: The holdings of eight collections of fungi have been examined for organisms isolated from wood and/or trees. Further selection of these fungi has been made according to their reported ability to produce volatile, biologically active metabolites. It is emphasized that the isolates in the collections do not necessarily produce such metabolites. The list of fungi fulfilling these conditions is slightly augmented by reports we have found in the literature, where the fungi concerned have not yet been deposited. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 125 publications
0
21
0
1
Order By: Relevance
“…Fungi, on the other hand, commonly make longchain hydrocarbons along with a series of low-molecularmass alcohols, ethers, esters, ketones and terpenoids (Sunesson et al, 1995). Wood-inhabiting fungi seem to make a wide range of volatile products (McAfee &Taylor, 1999). The production of these volatile products by microbes is dependent upon the environmental conditions, the support medium and the microbial species being studied (Sunesson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi, on the other hand, commonly make longchain hydrocarbons along with a series of low-molecularmass alcohols, ethers, esters, ketones and terpenoids (Sunesson et al, 1995). Wood-inhabiting fungi seem to make a wide range of volatile products (McAfee &Taylor, 1999). The production of these volatile products by microbes is dependent upon the environmental conditions, the support medium and the microbial species being studied (Sunesson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Many fungi are known to produce octane, 1-octene and lower-molecular-mass hydrocarbons (McAfee & Taylor, 1999;Sunesson et al, 1995). Since G. roseum (NRRL 50072) produces a number of volatile hydrocarbons along with some corresponding oxygenated products (acids, esters, ethers and alcohols), it seemed important to determine if a modification of the environmental and cultural conditions of this organism would result in the production of more reduced compounds that are even more closely related to diesel fuel (Stinson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While fungi producing volatile organic compounds (VOCs) have been isolated and studied chemically in the past 30-40 years, none have been found that have such a comprehensive spectrum of antimicrobial activity as that of Muscodor albus (Strobel et al, 2001;McAfee & Taylor, 1999). M. albus was the first endophytic fungus demonstrated to produce VOCs with broad-spectrum killing propeties against other microbes, including plant and human pathogens (Strobel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi represent a rich source of bioactive natural products and have been studied for their production of volatile organic compounds (VOCs) (McAfee & Taylor, 1999;Strobel, 2006;Strobel et al, 2001). Microbial VOCs are typically low-molecular-mass organics derived from both primary and secondary metabolism pathways that include compounds used as industrial chemicals and aroma components (Korpi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%